Modul kesediaan kerjaya berdasarkan teori Cognitive Information Processing (CIP) - Mahmud, Mohd Izwan; Mohd Noah, Sidek; Ahmad, Jamaludin; Wan Ahmad, Wan Marzuki (Faculty of Education, University of Malaya, 2016)
Career education involves structured teaching and learning activities to provide a platform for students in understanding their potential, the working world and enhancing their specific skills in career decision making. This study aimed at developing a structured career module based on the Cognitive Information Processing (CIP) theory and using the Model Pembinaan Modul Sidek (MPMS) as a guideline for the module preparation process. The content of the module was identified from extensive critical and analyitical review of literature. The study resulted in a draft module having three sub-modules namely knowledge, decision making and executive processing. These three sub-modules were further split into fourteen compiled activities and eight units. Thus, it is recommended that a follow-up study be done to explore the draft module’s validity and reliability.